On the location of the peaks of least-energy solutions to semilinear Dirichlet problems with critical growth. (26th September 2002) - Souto, Marco A. S.
Abstract : We study the location of the peaks of solution for the critical growth problem− ε   2 Δ u + u = f ( u ) + u   2 * − 1, u > 0 inΩ, u = 0 on∂ Ω, whereΩ is a bounded domain;2 * = 2 N / ( N − 2 ), N ≥ 3, is the critical Sobolev exponent andf has a behavior likeu p, 1 < p < 2 * − 1 .